1982
DOI: 10.1007/bf00121117
|View full text |Cite
|
Sign up to set email alerts
|

Models and observations of the growth of the atmospheric boundary layer

Abstract: The evolution of the mixed layer during a clear day can be described with a slab model. The model equations have to be closed by a parameterization of the turbulent kinetic energy budget. Several possibilities for this parameterization have been proposed. In order to assess the practical applicability of these models for the atmosphere, field experiments were carried out on ten clear days in 1977 and 1978. Within the accuracy of the measurements the mixed-layer height in fully convective conditions (at noon on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
161
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(171 citation statements)
references
References 22 publications
8
161
0
2
Order By: Relevance
“…By analyzing the turbulence kinetic energy (TKE) budget, it is possible to obtain a parametric expression which depends only on scaling parameters. These expressions have been evaluated with observations (Artaz and André 1980, Dubosclard 1980, Driedonks 1982, Culf 1992, Betts and Ball 1994, Angevine et al 1998, Hägeli et al 2000. By comparing the parameterized boundary layer depth or entrainment flux ratio against observations, the authors of some of these studies pointed to the importance of taking shear and dissipation contributions into account in the parameterizations.…”
Section: Introductionmentioning
confidence: 99%
“…By analyzing the turbulence kinetic energy (TKE) budget, it is possible to obtain a parametric expression which depends only on scaling parameters. These expressions have been evaluated with observations (Artaz and André 1980, Dubosclard 1980, Driedonks 1982, Culf 1992, Betts and Ball 1994, Angevine et al 1998, Hägeli et al 2000. By comparing the parameterized boundary layer depth or entrainment flux ratio against observations, the authors of some of these studies pointed to the importance of taking shear and dissipation contributions into account in the parameterizations.…”
Section: Introductionmentioning
confidence: 99%
“…The entrainment dynamics of sheared CBLs that are driven by both convection and wind shear, turned out to be a more challenging issue. Based on an extensive atmospheric observations Driedonks (1982) found that wind shear can significantly enhance the diurnal growth of fair weather CBLs, which rather well corresponded with prediction of a simple bulk model. However, as typical for atmospheric observations, uncertainties remained very high.…”
Section: Current Understanding Of Shear Effects On Entrainment In Cblssupporting
confidence: 75%
“…Deardorff et al, 1969;Deardorff and Wilis, 1985;Fedorovich et al, 2001b) or atmospheric observations (e.g. Stull, 1976a;Driedonks, 1982). However, if appropriate data are available, which is potentially always the case when using LES or DNS, we find this practice methodologically inconsistent.…”
Section: Particular Research Objectives With Respect To the Equilibrimentioning
confidence: 75%
See 2 more Smart Citations